A Placebo-controlled double-blinded test of the biodiversity hypothesis of immune-mediated diseases: Environmental microbial diversity elicits changes in cytokines and increase in T regulatory cells in young children - Roslund, Marja I; Parajuli, Anirudra; Hui, Nan; Puhakka, Riikka; Grönroos, Mira; Soininen, Laura; Nurminen, Noora; Oikarinen, Sami; Cinek, Ondřej; Kramná, Lenka; Schroderus, Anna-Mari; Laitinen, Olli H; et al. (Ecotoxicology and environmental safety, 2022)
BACKGROUND: According to the biodiversity hypothesis of immune-mediated diseases, lack of microbiological diversity in the everyday living environment is a core reason for dysregulation of immune tolerance and - eventually - the epidemic of immune-mediated diseases in western urban populations. Despite years of intense research, the hypothesis was never tested in a double-blinded and placebo-controlled intervention trial. OBJECTIVE: We aimed to perform the first placebo-controlled double-blinded test that investigates the effect of biodiversity on immune tolerance. METHODS: In the intervention group, children aged 3-5 years were exposed to playground sand enriched with microbially diverse soil, or in the placebo group, visually similar, but microbially poor sand colored with peat (13 participants per treatment group). Children played twice a day for 20 min in the sandbox for 14 days. Sand, skin and gut bacterial, and blood samples were taken at baseline and after 14 days. Bacterial changes were followed for 28 days. Sand, skin and gut metagenome was determined by high throughput sequencing of bacterial 16 S rRNA gene. Cytokines were measured from plasma and the frequency of blood regulatory T cells was defined as a percentage of total CD3 +CD4 + T cells. RESULTS: Bacterial richness (P < 0.001) and diversity (P < 0.05) were higher in the intervention than placebo sand. Skin bacterial community, including Gammaproteobacteria, shifted only in the intervention treatment to resemble the bacterial community in the enriched sand (P < 0.01). Mean change in plasma interleukin-10 (IL-10) concentration and IL-10 to IL-17A ratio supported immunoregulation in the intervention treatment compared to the placebo treatment (P = 0.02). IL-10 levels (P = 0.001) and IL-10 to IL-17A ratio (P = 0.02) were associated with Gammaproteobacterial community on the skin. The change in Treg frequencies was associated with the relative abundance of skin Thermoactinomycetaceae 1 (P = 0.002) and unclassified Alphaproteobacteria (P < 0.001). After 28 days, skin bacterial community still differed in the intervention treatment compared to baseline (P < 0.02). CONCLUSIONS: This is the first double-blinded placebo-controlled study to show that daily exposure to microbial biodiversity is associated with immune modulation in humans. The findings support the biodiversity hypothesis of immune-mediated diseases. We conclude that environmental microbiota may contribute to child health, and that adding microbiological diversity to everyday living environment may support immunoregulation.
Keywords: Children's Environmental Health; interleukin-17; Humans; Immune regulation; písek; Double-Blind Method; Biodiversity hypothesis; cytokiny; Interleukin-10; Placebo; Interleukin-17; Microbiota; dvojitá slepá metoda; lidé; Urban rewilding; předškolní dítě; Sand; biodiverzita; Cytokines; regulační T-lymfocyty; Bacteria; interleukin-10; T-Lymphocytes, Regulatory; Child, Preschool; Biodiversity